Preparação e atuação: o trabalho da atriz e do ator em simulação realística nas avaliações para formação nos cursos da medicina - Oliveira, Beatriz Ruiz Candolo Vilas Boas de (2023)
This artistic, qualitative research, with an exploratory bias, has as its investigation goals the preparation and performance of actors/actresses in medical simulation evaluations for the degree in medical courses, named Objective Structured Clinical Examination. I start from the main question: How to prepare actors/actresses to act as simulated patients in these evaluations? The premise of the research is to establish reflections around the theme, in addition to propose and analyze the possibility of preparation for the simulated patients. Experiences as simulated patient, as observer of an Objective Structured Clinical Examination and teaching an elective discipline in the Theater degree at the Federal University of Uberlândia were part of the process. I created, prepared and taught the discipline and it an experiment to prepare for acting as a simulated patient in medical exams. In order to study the possible results, in addition to considering my own observations, I collected perceptions from enrolled students and evaluators of medical tests through questionnaires, followed by a systematized analysis. Primarily, I used specific interdisciplinary bibliographies between theater and medicine, by authors such as Emerson Rossini, Raquel Mastey, Adilson Ledubino and Peggy Wallace. As well as medical education materials around the Objective Structured Clinical Examination and theater texts, more specifically improvisation and theater games, by authors such as Viola Spolin, Sandra Chacra, Ingrid Koudela and Johan Huizinga. Regarding the methodology employed, the project has multiple characteristics, among them, what Fortin and Gosselin understand as research in the arts and Ciane Fernandes's idea about practice as research for the study of performing arts.